2000
DOI: 10.1007/s004030000185
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the stratum corneum of scalp skin: studies in patients with alopecia areata and androgenetic alopecia

Abstract: Because of the presence of thick long hairs on the scalp, little information is available concerning the functional characteristics of the stratum corneum (SC) of scalp skin. We therefore conducted a functional study of the SC of lesional scalp skin of patients with alopecia areata and of patients with androgenetic alopecia. We compared the scalp with the cheek and the flexor surface of the forearm (volar forearm). The water barrier function of the scalp SC of both patient groups, in terms of transepidermal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 12 publications
1
49
1
Order By: Relevance
“…We think that the reason why the facial skin of adult women hardly becomes dry even in winter is that in contrast to the forearm it is covered with sebum due to the ample sebum secretion despite the environmental seasonal changes. In our former studies, we found that removal of the skin surface lipids from the cheek or scalp with ether even for a short period of time definitely decreased the skin surface hydration, which however, returned to former levels in a few hours with sebum secretion [6,15]. Such a quick recovery in the skin surface hydration state is never observed on the skin of the flexor surface of the extremities where sebum secretion is negligible.…”
Section: Discussionmentioning
confidence: 77%
“…We think that the reason why the facial skin of adult women hardly becomes dry even in winter is that in contrast to the forearm it is covered with sebum due to the ample sebum secretion despite the environmental seasonal changes. In our former studies, we found that removal of the skin surface lipids from the cheek or scalp with ether even for a short period of time definitely decreased the skin surface hydration, which however, returned to former levels in a few hours with sebum secretion [6,15]. Such a quick recovery in the skin surface hydration state is never observed on the skin of the flexor surface of the extremities where sebum secretion is negligible.…”
Section: Discussionmentioning
confidence: 77%
“…Scalp urticaria usually does not present with the classic findings of erythema and edema, because of the scalp's skin structure. Rather, patients complain of irritation, pruritus, stinging, or burning of the scalp [44,45] .…”
Section: Urticarial Lesionsmentioning
confidence: 99%
“…It is important in playing a role of drug partitioning from the vehicle to SC. Sebumderived lipids are especially abundant on the scalp skin (26). Sebum removal did not change DPCP deposition from the free control, suggesting that the outermost sebum partitioning was not a rate-limiting process for this drug.…”
Section: Discussionmentioning
confidence: 88%
“…Although nude mouse skin is thinner and more permeable as compared to human skin, it is still an alternative for skindelivery examination due to limited variability among individuals (25). Patients with alopecia areata or androgenetic alopecia often reveal lesional scalp skin with a reduced epidermal barrier function (26,27). Since DPCP and minoxidil are most frequently applied for scalp treatment, nude mouse skin is especially suitable as the alternative for lesional scalp skin because the permeability of the scalp is higher than that of the other anatomical regions (28).…”
Section: Discussionmentioning
confidence: 99%